2019
DOI: 10.1108/oth-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Education for employability: the ePortfolio from school principals’ perspective

Abstract: Purpose The purpose of this paper is to explore the question of whether the school principals would use an educational ePortfolio for recruiting purposes. Design/methodology/approach To examine whether the school principals are willing to use the educational ePortfolio for recruiting purposes, a survey was carried out among 35 school principals. The final version of the survey was audited by a panel of four experts on education and instructional technology, and a board member of the Spanish Association of Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Note: Own development based on [9] It was proved that students who are not motivated to learn have difficulty learning and developing learning skills. E-portfolio documents achievements and success in the learning process, which allows students to easily analyze them [22].…”
Section: Fig 1 the Development Of Self-regulated Learning Skills Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Note: Own development based on [9] It was proved that students who are not motivated to learn have difficulty learning and developing learning skills. E-portfolio documents achievements and success in the learning process, which allows students to easily analyze them [22].…”
Section: Fig 1 the Development Of Self-regulated Learning Skills Thmentioning
confidence: 99%
“…Thus, these are "web-based collections of learning artifacts generated by students (documents, multimedia projects, speeches, images, etc.) and related reflections focused on learning and growth" [9]. A modern e-portfolio is a platform that can be used to compile, organize, and develop a digital presentation; it can be updated and adapted for different purposes and audiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study concluded that ePortfolios will be used in the same way as 'hard copy' job applications (Rowley & Dunbar-Hall, 2015), with another seeing it as a supplementary resource (Yu, 2012). In this more minor utilisation of the platform, a URL link to an online ePortfolio would be submitted with the standard application to use during initial screening and shortlisting (Ciesielkiewicz, 2019;Leece, 2005;Ndoye et al, 2012;Weber, 2018). While LinkedIn may be considered a form of online portfolio, it was not used in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported that their participants saw ePortfolios as being useful during the interview process, however, two studies felt that the interview stage was not appropriate, with the remaining seven studies not commenting on this stage of the recruitment process. Five studies had participants who felt there was a benefit to using an ePortfolio to distinguish between candidates (Painter & Wetzel, 2005) and make the final hiring decision (Ciesielkiewicz, 2019;Painter & Wetzel, 2005;Snoeyink & Meyer, 2007;Weber, 2018;Yu, 2012).…”
Section: Current and Expected Use Of Eportfolios By Recruitersmentioning
confidence: 99%